Exploring career anchors among occupational health nurses in Japan: A qualitative study. Issue 1 (7th July 2016) - Kubo, Yoshiko; Hatono, Yoko; Kubo, Tomohide; Shimamoto, Satoko; Nakatani, Junko; Burgel, Barbara J
Abstract: Aim: This study examined the career anchor characteristics that are possessed by Japanese occupational health nurses. Method: Sixteen occupational health nurses participated in the semistructured interview. Data analyses were conducted using descriptive qualitative methods. Results: The data showed the following five categories: practices concerning relationships and positions; development of occupational health practices; management skills for effective work; practices that are approved inside and outside the organization; and work and private life considerations. Conclusions: This study described the career anchors among occupational health nurses in Japan. The participants emphasized the following: the importance of maintaining good cooperative relationships with workers and supervisors; balancing professional and organized labor; and practicing effective occupational health services. Moreover, the occupational health nurses emphasized receiving approval from inside and outside of the organization. These results were consistent with the actual practices of occupational health nursing.